2021
DOI: 10.3390/antiox10060870
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Exercise and Astaxanthin Supplementation: Are There Additive or Synergistic Effects?

Abstract: A healthy lifestyle is essential for maintaining physical and mental health. Health promotion, with a particular emphasis on regular exercise and a healthy diet, is one of the emerging trends in healthcare. However, the way in which exercise training and nutrients from dietary intake interact with each other to promote additive, synergistic, or antagonistic effects on physiological functions leading to health promotion, and the possible underlying biomolecular mechanisms of such interactions, remain poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…For endurance athletes interested in AX supplementation, the current recommendations for dosages range from 4–12 mg/d to elicit a potential ergogenic effect [ 24 , 25 ]. As outlined earlier, AX may exert a greater range of benefits for those recreationally trained compared to the elite endurance athlete, although this is simply a hypothesis drawn from the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For endurance athletes interested in AX supplementation, the current recommendations for dosages range from 4–12 mg/d to elicit a potential ergogenic effect [ 24 , 25 ]. As outlined earlier, AX may exert a greater range of benefits for those recreationally trained compared to the elite endurance athlete, although this is simply a hypothesis drawn from the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AMPK’s downstream effects, such as its ability to induce mitochondrial biogenesis through its regulation of PGC1-α gene expression, suggest that supplements such as AX may offer a metabolic and training advantage when dosed appropriately and supplemented chronically. When reviewing the evidence from AX supplementation in animal models with markers of endurance performance as the dependent variable of interest, the data are overwhelmingly positive [ 25 ]. While these findings from animal models do have important implications for the endurance athlete, similar studies in humans are currently limited and mixed, as detailed below.…”
Section: Astaxanthin: Nature’s Most Powerful Carotenoidmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is less available evidence about the precise mechanism by which ASX supplementa-tion acts, it is postulated that the favorable effects of ASX may be attributed to its impact on the secretion of adipokines, akin to other bioactive chemicals such as capsaicin. Although a recent review study found that combined ASX supplementation and exercise did not improve exercise performance [29], it is unknown whether a combination of ASX supplementation and exercise produces beneficial effects on metabolic health in obese individuals. Furthermore, the effects of ASX supplementation on adipokines in the present study are currently unclear [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on healthcare emphasizes regular exercise and a healthy diet. How diet and exercise training interact to produce synergistic or antagonistic effects on physiological functions that lead to health promotion and the possible mechanisms underlying such interactions are still poorly understood [ 22 ]. The combination of functional food consumption and exercise can cause changes in body metabolism [ 23 ].…”
Section: Introductionmentioning
confidence: 99%